IMPLEMENTASI MODUL PEMBELAJARAN BERBASIS PROJECT BASED LEARNING PADA MATERI BANGUN RUANG DAN STATISTIKA - Astriani, Linda; Widyasari, Nurbaiti; Muthmainnah, Rahmita Nurul; Heriyana, Tio (Fakultas Ilmu Pendidikan Universitas Muhammadiyah Jakarta, 2025)
The current mathematics learning process has not fully succeeded in incorporating project-based modules. The Independent Curriculum emphasizes the use of Project-Based Learning (PjBL), where students engage in real-world projects to solve problems or answer specific questions. This approach aims to foster critical thinking, collaboration, and creativity among students. This study focuses on implementing a project-based statistical spatial module tailored for elementary school students. The research utilized qualitative methods, involving a population of 15 fifth-grade students from an Islamic Elementary School in South Jakarta. Data collection techniques included observation and testing. The application of PjBL made mathematics learning more engaging and meaningful. The projects designed not only enhanced students' curiosity but also provided opportunities to develop their creativity, critical thinking, and teamwork skills. Through this approach, students not only gain mathematical knowledge but also cultivate essential skills for their present and future lives.